1993
DOI: 10.1042/cs0840095
|View full text |Cite
|
Sign up to set email alerts
|

Muscle weakness in women occurs at an earlier age than in men, but strength is preserved by hormone replacement therapy

Abstract: 1. The time-course of the age-related decline in specific muscle force (maximum voluntary force per cross-sectional area) in men and women was determined by measuring the maximum voluntary force and cross-sectional area of the adductor pollicis muscle in 273 subjects aged 17-90 years (176 men, 30 premenopausal women and 67 peri- or post-menopausal women who were not receiving hormone replacement therapy). 2. To determine whether the loss of specific muscle force is hormone-dependent in women, we studied a furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
330
5
6

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(361 citation statements)
references
References 14 publications
12
330
5
6
Order By: Relevance
“…Greater muscle mass, testosterone and GH levels and the lesser propensity to dysregulation of the hypothalamicadrenal axis and cortisol secretion may protect males from physical decline (15)(16)(17)(18)(19). A distinctive age-related change in the immune system probably makes men more vulnerable to infections and less prone to chronic conditions which are ultimately responsible for muscle loss (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Greater muscle mass, testosterone and GH levels and the lesser propensity to dysregulation of the hypothalamicadrenal axis and cortisol secretion may protect males from physical decline (15)(16)(17)(18)(19). A distinctive age-related change in the immune system probably makes men more vulnerable to infections and less prone to chronic conditions which are ultimately responsible for muscle loss (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…ERs are also found in the skeletal muscle cells, making skeletal muscle tissue responsive to estrogens (Lemoine, et al 2003, Wiik, et al 2005). There are indications that dramatically decreasing level of circulating 17ÎČ-estradiol (E 2 ) at the time of menopause contributes to age-associated muscle weakness (Phillips, et al 1993, Sipila, et al 2001. Our previous studies have shown that the use of estrogen-or estrogen and progesterone -based hormone replacement therapy (HRT) is associated with better muscle quality properties, such as a positive muscle-fat ratio within the muscle compartment, as well as improved muscle performance characteristics like muscle power and mobility (Ronkainen, et al 2009, Finni, et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that hormone replacement therapy (HRT) prevents the shift in body fat distribution to a more central location (5)(6)(7) and diminishes the loss of muscle strength (8)(9)(10)(11)(12)(13)(14)(15). Unfortunately, HRT use is accompanied by adverse side effects, such as an increased risk of breast cancer and cardiovascular disease (16), and for this reason its long-term use is not advocated.…”
Section: Introductionmentioning
confidence: 99%